Hustle Culture as a Contemporary Form of Idolatry: A Theological Analysis of the Old Testament - Ferry Sonny Lumintang; Ramli Sarimbangun (Jurnal Multidisiplin Indonesia, 2026)
The hustle culture phenomenon in modern society reflects a significant shift in life orientation, where success and productivity become the primary sources of identity and meaning. Therefore, this study aims to analyze hustle culture as a form of contemporary idolatry from the perspective of Old Testament theology and affirm its relevance to today's faith life. This research is important because it provides a critical theological framework for reading modern social phenomena that are often considered neutral but actually contain profound spiritual implications. The method used is a qualitative approach through the study of literature with theological-biblical analysis of key texts, especially Exodus 20:3 and Deuteronomy 8:17–18, and supported by contemporary theological literature. The main argument of this study states that hustle culture is a form of modern idolatry that is non-material, where success and career function as "gods" that demand total loyalty and devotion, thus shifting the orientation of faith from God to human achievement. The results of the study show that the concept of idols in the Old Testament was not limited to physical objects but included everything that took over God's position in the human heart. Thus, hustle culture can be understood as a manifestation of idolatry in a new form that is structural and cultural. This study concludes that critical theological reflection is needed to reframe the orientation of human life to be centered on God as the primary source of identity, meaning, and hope.